STRUGGLE FOR LIFE OF ROBINSON CRUSOE IN GEORGE MILLER AND RODNEY K. HARDY’S ROBINSON CRUSOE (1997): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KURNIAWAN , EDI (2011)
The problem of this study is to reveal how the struggle of life in major character is. The objectives of the study are to analyze the major character in Robinson Crusoe movie based on Individual Psychological Approach.